Superficial Mycoses in Old People Residents of the Geriatrical Unit "Monseñor Dr. Rafael Arias Blanco", Juan Griego, Nueva Esparta State, Venezuela - Sara Centeno; Marguel Marcano (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2007)
The superficial mycoses frequency was evaluated in a population of 71 old people between 62 and 98 years old, males and females, residents of a geriatrical unit, during the October 2005-February 2006 period, of which 49 presented a suggestive diagnosis. A direct exam with KOH at 10% was done to the obtained samples, which were cultivated in fungobiotic agar and incubated during 15 days at room temperature. The colonies of filamentous bacteria were identified by macro and microscopic characteristics, while leavenings of Candida genus by the API 20 C AUX® identification system. The obtained results were analyzed trough method of percentage analysis (%) and test of Chi-square (2). 40 (81.63%) cases resulted positive, of which 82.50% were cutaneous candidosis, being ungual candidosis the most frequent, followed by la tinea unguium (12.50%) and onychomycosis due to non-dermatophytic fungi (5.00%). No case of pityriasis versicolor was detected. C. albicans was the fungus most frequently isolated (64.81%), generally in nails of feet, followed by C. parapsilosis (12.96%) and Trichophyton mentagrophytes (5.56%). A high incidence of cutaneous candidosis was observed at old people, which was favoured by the physical conditions common in them, concomitant disease, deficiency in cellular immunity and certain predisponent factors, such as life style, the use of closed shoes, warm weather and the humidity in the region where they live.